Structure and crystallization of lanthanum fluorozirconate glasses - Ribeiro, SJL; Dugat, P.; Avignant, D.; DexpertGhys, J. (Elsevier B.V., 1996)
Glasses with compositions (1-x)ZrF4-xLnF(3), 0.2 less than or equal to x less than or equal to 0.4 and Ln = La or La, Eu have been synthesized and investigated using differential scanning calorimetry, X-ray diffraction, Raman scattering and Eu3+ optical spectroscopy. Single-phase polycrystalline lanthanum fluorozirconates with Zr/Ln ratio equal to 1, 2 and 3 have been investigated using the same techniques for comparison. The crystalline phases LnZrF(7), LnZr(2)F(11), LT-LnZr(3)F(15) (orthorhombic) and HT-LnZr(3)F(15) (trigonal) have been characterized in the recrystallized glasses and in samples spontaneously crystallized from the melt. Another phase has also been observed but remains undefined, the Raman scattering spectra of the vitreous samples are related to the vibration modes of [ZrF6] isolated octahedra, and of [ZrF7] and [ZrF8] structural units with bridging fluorine ions. The Eu3+ fluorescence data are related to a predominant local environment of the lanthanide ions in the glasses similar to that of the lanthanide in LnZrF(7).